PENGARUH PROMOSI KESEHATAN TERHADAP PENGETAHUAN DAN SIKAP IBU DALAM PENATALAKSANAAN GIZI BURUK DI WILAYAH KERJA PUSKESMAS MEDAN DELI TAHUN 2018 - Naibaho, Clara C; Gultom, Dameria (Jurnal Kesehatan Masyarakat dan Lingkungan Hidup, 2019)
Health Promotion is to revitalize education with the term health promotion, if health education is defined as an effort to change behavior, but also changes. Malnutrition is a condition of lack of consumption of nutrients caused by low protein energy consumption in daily food, so that there are clinically three types, namely marasmus, kwashiorkor, and marasmus kwashiorkor. The prevalence of malnutrition and malnutrition was 19.6%, in 2007 18.4%, and in 2010 it increased to 17.9%. Based on data obtained by Medan Deli Health Center that there are 44 toddlers with problems with malnutrition. This type of research is Quasi Experiment research and the variables used are, knowledge, and attitude. The research sample was 44 people. Data collection uses questionnaires and data analysis techniques with T Test where questionnaires were given before (pretest) and after (posttest) intervening with respondents. The results of the analysis showed that there was a relationship between the effect of health promotion on knowledge (p = 0,000) and attitudes (p = 0,000) and the average value of knowledge before intervention was 28.86 while after intervention 34.75 as well as attitude variables before intervention 26, 84 and after intervention 38.84. Therefore, respondents must pay more attention to their children's nutrition in order to reduce the incidence of nutrition, especially malnutrition. Efforts made for the community are by encouraging mothers to always take their children to the posyandu, and provide full immunizations to toddlers so they can monitor the progress of these children.